The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep37487
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis between an evolved abscisic acid-overproducing mutant Botrytis cinerea TBC-A and its ancestral strain Botrytis cinerea TBC-6

Abstract: Abscisic acid (ABA) is a classical phytohormone which plays an important role in plant stress resistance. Moreover, ABA is also found to regulate the activation of innate immune cells and glucose homeostasis in mammals. Therefore, this ‘stress hormone’ is of great importance to theoretical research and agricultural and medical applications. Botrytis cinerea is a well-known phytopathogenic ascomycete that synthesizes ABA via a pathway substantially different from higher plants. Identification of the functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…Moreover, Bcstc5/Bcaba5 appeared to be approximately sixfold more highly expressed in ATCC58025 than in B05.10. As ABA is a compound of interest for biotechnology companies, several screening and mutagenesis programs were conducted to improve the ability B. cinerea to produce this compound at an industrial scale, i.e., up to 6 g l −1 (Gong et al ., ; Ding et al ., ; Shi et al ., ). The resulting ABA‐overproducing strains like ATCC58025 are impaired in conidiation and other developmental processes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, Bcstc5/Bcaba5 appeared to be approximately sixfold more highly expressed in ATCC58025 than in B05.10. As ABA is a compound of interest for biotechnology companies, several screening and mutagenesis programs were conducted to improve the ability B. cinerea to produce this compound at an industrial scale, i.e., up to 6 g l −1 (Gong et al ., ; Ding et al ., ; Shi et al ., ). The resulting ABA‐overproducing strains like ATCC58025 are impaired in conidiation and other developmental processes.…”
Section: Discussionmentioning
confidence: 97%
“…For the Bcaba genes, no candidate gene encoding a possible pathway‐specific regulator could be found at the Bcstc5/Bcaba5 locus nor at the Bcaba1 to Bcaba4 locus. In addition, previous data indicated that Bcaba1 to Bcaba4 genes are not always strictly co‐expressed in the ATCC58025 strain (Siewers et al ., ) nor in another ABA‐overproducing strain (Ding et al ., ). Together these data do not support an ABA‐specific transcription factor but would rather suggest that the Bcaba genes could be directly under the control of global regulators.…”
Section: Discussionmentioning
confidence: 99%
“…Pairwise comparisons against HUVEC cultivated on TCPS, PCL or PCL-Gl-glu matrices are presented in Table 2. To potentially account for strength of the effects on phenotype, all genes were divided into categories based on RPKM: very low (0 < RPKM < 1), low (1 < RPKM< 10), average (10 < RPKM < 100), high (RPKM > 100), very high expression (RPKM > 1000), similar to previous studies [61,62] (Tables 2 and 3). Genes expressed at a very low level (0 < RPKM < 1) were excluded from further analysis.…”
Section: Transcriptome Profilingmentioning
confidence: 99%
“…Furthermore, several studies support the role of ABA in promoting virulence in plant‐ Botrytis interactions. ABA overproduction has been associated with enhanced virulence in some strains (Siewers et al , Gong et al , Ding et al ) and treatment with exogenous ABA was shown to promote virulence (Shaul et al ). The WRKY33 transcription factor is required for the downregulation of plant ABA biosynthesis and thus promotes immunity against Botrytis (Liu et al ).…”
Section: Introductionmentioning
confidence: 99%